INOVASI PROGRAM PEMBELAJARAN KETERAMPILAN BERPIKIR KRITIS MELALUI MODEL PEMBELAJARAN KONSTEKSTUAL PADA POKOK BAHASAN LARUTAN PENYANGGA - Widiyowati, Iis Intan (PROSIDING SEMINAR KIMIA, 2014)
A study has been conducted which is aimed to find out about critical thinking skill of Senior High School Students in Buffer Solution learning with Contextual Teaching and Learning. This study used One Group Pre-test-Post-test Design which involved 42 Senior High School students of class XI. The data that was obtained from the pre-test and post-test mark to find out about critical thinking skill. The excellence of the program was could show relationship among concept, develop concept understanding and critical thinking skills of student with Contextual Teaching and Learning. Generally, the learning model with Contextual Teaching and Learning can motivate students to learn, and it can improve the complex thinking ability